Forgetting Cleopatra - Hodgson, Elizabeth (Shakespeare and Consciousness, 2016)
Hodgson examines the reciprocal operations of remembering and forgetting in relation to liturgical and theatrical acts and objects that problematize the memorialization of the dead in early modern consciousness. Hodgson emphasizes the distributed and collective function of both memorizing and forgetting in theatrical production, and she links this to social memory in collective and individual religious practices that require self-examination. Citing Pierre Nora’s work on memory objects, she identifies a paradox in the ability of monuments to both establish social memory and allow mourners to forget. Turning to Antony and Cleopatra, she considers how characters consider and construct problematic afterlives linked to their anticipation of individual and social forgetfulness. This is emphasized in a detailed reading of Cleopatra’s imaginary oblivion in the monument.